RESEARCH ON FUZZY CONTROL SIMULATION OF CVT RATIO BASED ON ENGINE SPEED REGULATION CHARACTERISTICS - GUO Wei; JIA GaoXiang; ZHANG Wu; CHEN Ya (Jixie qiangdu)
According to the load characteristics and speed regulation characteristics of the engine,the steady-state torque model is established and the optimum power and economy curves of engine are determined. Then the engine target speed is obtained by using the economic weighting coefficient method. The power transmission system is simplified into a double rotating mass model. Through mathematical model of the whole vehicle,the physical model is established by using Simulink,and a speed ratio fuzzy control method based on the speed regulation characteristic of engine is proposed,then the starting condition,braking condition and circulating condition are simulated respectively. The simulation results show that the following effect of actual speed ratio to target speed ratio can be realized well. It shows that the speed ratio fuzzy control method based on the characteristics of engine speed regulation can be well applied to speed ratio control.